2016
DOI: 10.1111/ans.13470
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic resection of non‐colorectal non‐endocrine liver metastases

Abstract: Hepatic resection can be achieved safely for NCNELM. Patient selection is key, along with a standardized surgical and anaesthetic technique. Patients should be rigorously investigated to exclude disseminated disease and multidisciplinary discussion must take place prior to surgery. Patients with NCNELM should not routinely be excluded from liver resection and selected patients may benefit from resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 23 publications
3
15
0
Order By: Relevance
“…We found similar results for metachronous disease [9,16,23,26,27]. At present, there is no guideline indication concerning the treatment of metachronous distant metastases of esophageal cancer.…”
Section: Surgerysupporting
confidence: 81%
See 2 more Smart Citations
“…We found similar results for metachronous disease [9,16,23,26,27]. At present, there is no guideline indication concerning the treatment of metachronous distant metastases of esophageal cancer.…”
Section: Surgerysupporting
confidence: 81%
“…One third of the patients who were analyzed in the study had metastasectomy of 1 to 2 liver metastases during the same EC surgery. These findings are closely mirrored by Gandy et al [23], with a 60% 5-year OS after liver resection in a cohort of 48 patients, 2 of which were affected by liver OEC. In a retrospective study including 96 patients, Wang et al [15] reported that a small subset of 14 patients who were treated with a multimodal approach including liver resection showed a more favorable prognosis compared to patients who did not undergo surgery.…”
Section: Surgerysupporting
confidence: 80%
See 1 more Smart Citation
“…19 Studies from 2009 onward have demonstrated an improvement in disease-free survival and total survival of patients undergoing hepatic metastasectomy regardless of the types of primary neoplasias. 7,9,[20][21][22][23][24][25] Based on previous studies, the mean total survival for patients with stage IV ovarian epithelial cancer varied between 15 and 29 months, with a total survival of 20% at 5 years. 18 In the current study, diseasefree survival was better in patients with peritoneal seeding metastasis; however this result was nonsignificant and the overall survival analysis showed no difference among these patients.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Bacalbasa et al reported a clear difference in disease free-survival and overall survival in favor of the peritoneal seeding liver metastasis group. 1 Rodríguez et al argued that this advantage in disease-free survival and overall survival, described in some reports, 1,7,[20][21][22][23][24] was due to an indirect effect, because these patients could have gained the benefit of complete cytoreduction that could have influenced the prognoses. 26…”
Section: Discussionmentioning
confidence: 99%